Surgicel Mimicking Acute Vessel Occlusion after Carotid Endarterectomy: A Case Report. Issue 2 (June 2014) - Morris, Rhys; Bosanquet, David C.; Mapstone, Julia; James, Dorrien; Fligelstone, Louis
Surgicel (oxidized regenerated cellulose; Ethicon, Somerville, NJ) is widely used in surgery to achieve hemostasis but can interfere with postoperative imaging. A patient was noted to have lateralizing neurologic deficits immediately after a carotid endarterectomy, with an internal carotid artery flow void on duplex. However, at return to the operating theater, no flow void was noted after Surgicel was removed. Reapplying Surgicel around the vessel recreated this acoustic shadow, confirming this ultrasonographic finding was simply an artifact. Surgicel is known to trap air within the interstices of the gauze. This phenomenon can obscure vessel flow to mimic an occlusion on duplex imaging.